Pd(II) Complexes with Nitrogen-oxygen Donor Ligands: Synthesis, Characterization and Catalytic Activity for Suzuki-Miyaura Cross-coupling Reaction - M.T Amalina; B Hadariah; K Karimah; W.I.W Nazihah (ASEAN Journal on Science and Technology for Development, 2014)
Inexpensive bidentate Schiff base ligands (O1, O3) and their Pd(II) complexes (OPd1, OPd3) were successfully synthesized and characterized using CHN elemental analysis, FTIR, 1H and 13C NMR, melting point determination, molar conductivity and magnetic moment. It revealed that these Schiff bases behaved as bidentate ligands in their complexes. The spectral data indicated that the ligands co-ordinated through the phenolic oxygen and the azomethine nitrogen atoms. Magnetic momentdata suggested the existence of square planar Pd(II) complexes, while non-electrolytic behaviour indicated the absence of counter ions in chloroform. The Pd(II) complexes showed good catalytic activities for Suzuki-Miyaura cross-coupling reaction between iodobenzene with phenylboronic acid at 1.0 mmol% catalyst loading.